2006
DOI: 10.1016/j.neuroscience.2006.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-mediated supersensitivity of 5-HT2A receptors in hypothalamic paraventricular nucleus is a withdrawal-induced phenomenon

Abstract: We previously reported that treatment and withdrawal from cocaine increases: (1) serotonin 2A (5-HT 2A ) receptor-mediated neuroendocrine responses, and (2) GÎ q and GÎ 11 G-protein levels in the hypothalamic paraventricular nucleus (PVN) at 48 h post-treatment. This study investigates changes in the initial 24 h of withdrawal to discern whether 5-HT 2A receptor supersensitivity is due to cocaine treatment or is induced during the withdrawal period. We report here increases in 5-HT 2A receptormediated neuroend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
(40 reference statements)
2
13
0
Order By: Relevance
“…Plasma prolactin and corticosterone concentrations were determined by radioimmunoassays as previously described [7]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma prolactin and corticosterone concentrations were determined by radioimmunoassays as previously described [7]. …”
Section: Methodsmentioning
confidence: 99%
“…The pellet was incubated with extraction buffer II with protease inhibitor cocktail for 30 mins at 4°C under gentle agitation and centrifuged 16,000 × g for 15 mins at 4°C to isolate the membrane fraction contained in the supernatant. Expression of membrane-associated 5-HT 2A receptors in PVN was determined by Western blot as previously described [7]. Films were analyzed densitometrically using Scion Image software (Scion Corporation, Frederick, MD, USA) as previously described [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Previous studies have suggested that withdrawal from cocaine sensitizes 5-HT 2A R Rothman, 1996, 1998;Carrasco et al, 2006;Carrasco and Battaglia, 2007), which may contribute to relapse, particularly as antagonists at 5-HT 2A R are able to block cue-and cocaine-primed reinstatement (Fletcher et al, 2002;Filip, 2005;Nic Dhonnchadha et al, 2009;Murnane et al, 2013b). It is important to note that the highest expression of 5-HT 2A R in the brain is on the dendrites of layer V cortical pyramidal glutamatergic cells (Cornea-Hebert et al, 1999;Jakab and Goldman-Rakic, 2000;Miner et al, 2003).…”
Section: Cortical Dysregulation and 5-ht 2a/c Receptor Functionmentioning
confidence: 99%
“…Cocaine exposure has also been reported to affect density and/or function of post-synaptic 5HT receptors, ranging from decreases in 5HT3 receptors in the nucleus accumbens shell of rats sensitized to cocaine (Ricci, Stellar & Todtenkopf, 2004) to reduced sensitivity of 5HT1A receptors (Baumann & Rothman, 1998). Cocaine exposure and withdrawal also have been reported to affect 5HT2A receptor expression and function, although no consensus has been reached as to the exact nature of these effects (Carrasco & Battaglia, 2007; Carrasco, Van de Kar, Sullivan, Landry, Garcia, Muma et al, 2006; Huang, Liang, Lee, Wu & Hsu, 2009). Overall, chronic cocaine clearly results in an altered state of the serotonin system, which could contribute to the development of cocaine dependence.…”
Section: Monoamine Transporters As Molecular Targets For Medication Dmentioning
confidence: 99%